Fault Diagnosis and Cause Analysis of Planetary Gear Trains in Gearboxes - Wang Zishun; Wang Yunlang; Zhao Donghui (Jixie chuandong)
Comprehensively utilizing various technical means, such as vibration signal analysis, endoscopy, macroscopic observation, metallographic analysis, scanning electron microscopy (SEM) analysis, energy dispersive spectroscopy (EDS) analysis, and mechanical performance experiments, a fault diagnosis and cause analysis were conducted for the radial cracking phenomenon along the tooth groove of a certain type of wind power gearboxes. The abnormal vibration was revealed through vibration signal analysis, and the characteristics of abnormal vibration was determined through spectrum analysis and time domain feature extraction. The fault location was confirmed through endoscopic inspection. After disassembly, SEM inspection were used to confirm the presence of a large-sized inclusion at the crack source, and the composition of the inclusion was determined through EDS, further analyzing and determining the entire process of gear penetration cracking. By comprehensive analysis, the cause and location of the fault were determined, which provides scientific basis for equipment maintenance, and improves production efficiency and equipment life, while reducing fault loss and maintenance costs.